67 Prostate-Specific Antigen (PSA) Screening Rates in the United States, 2010–2015: Implications for Practice Interventions. (11th January 2018) - Shahangian, Shahram; Fan, Lin; Taylor, Thomas
Abstract: Prostate-specific antigen (PS)A is the most commonly used cancer screening test in men. The US Preventive Services Task Force recommended against PSA screening of all men regardless of age in 2012, a recommendation endorsed by the American Academy of Family Physicians and the American College of Preventive Medicine. By 2013, the American Cancer Society, the American Urological Association, and the American College of Physicians had recommended offering PSA screening to men between 50 and 69 years of age with at least 10 years of remaining life expectancy, but only after a process of informed and shared decision-making. The objective of this study was to evaluate the rate of PSA screening and its trend in different age groups from 2010 through 2015 using large databases covering all men insured by Medicare plus one-third of all privately insured men in the US. Claims data for men under 65 years of age were collected using Truven Health Analytics' MarketScan database for commercial claims and encounters in 2010 to 2015 (9.9–16.6 million men). For men aged 65 years or older, claims data for the entire Medicare-insured population were evaluated using the Centers for Medicare and Medicaid Services virtual research data center encompassing 17.7–21.8 million men. A two-sided Poisson regression was used to determine P for trend using Bonferroni correction to adjust for the number of age groups. To consider PSA testing for screening only, all claims with any one or more of 62 prostate or urinary conditions implying use of testing for purposes other than screening were deleted. PSA-based screening rates in 2010 to 2015 were as follows: 2% in men age 30–39, 5%-6% in men age 40–49, 29%-31% in men age 50–59, 33%-36% in men age 60–64, 9%-12% in men age 65–69, 11%-14% in men age 70–74, and 6%-9% in men older than 74. There were no significant temporal trends in men aged 30–39 years ( P = .18), 50–59 years ( P = .08), 65–69 years ( P = .16), 70–74 years ( P = .05), and older than 74 years ( P = .16). There were significant downward trends in men aged 40–49 years ( P = .005) and 60–64 years ( P = .003). For all age groups, PSA screening rate decreased from 2010 to 2015 by 1%, 6%, 2%, 6%, 9%, 13%, and 10%, respectively, for men aged 30–39, 40–49, 50–59, 60–64, 65–69, 70–74, and greater than 74 years (1%-13% decrease in PSA screening rate for the seven age cohorts). All medical organizations recommend against PSA screening of men younger than 50 and older than 69, but a substantial proportion of younger (2%-6%) and older (6%-14%) men still are screened with PSA, contrary to all existing practice guidelines. Further research is needed to understand the reasons for overuse of PSA screening in order to identify more effective means to prevent it.